PROCEEDINGS BEFORE THE POLICE, PROSECUTOR'S OFFICE, AND COURT - Chairul Aman; Bustomi Bustomi (Jurnal Abdisci, 2026)
Abstrak. Background. The procedures and mechanisms of the criminal justice system regarding examination during the investigation and prosecution phases are conducted by the police and the public prosecutor in the pre-prosecution process. Aims. This community service aims to clarify the processes that occur before the police, the prosecutor's office, and the court. Methods. This community service initiative incorporates conversations and presentations by resource individuals during the Coffee Break event. Result. In a criminal justice system, multiple steps must be navigated. The steps commence with investigation, prosecution, trial, court examination, verdict delivery, and execution of criminal sentences. During the Police Report phase, the police conduct inquiries and investigations in criminal situations, as per Perkap number 14 of 2012 regarding Criminal Investigation Management. During the transition from the National Police Investigator to the Public Prosecutor, the Prosecutor is required to assess the evidence acquired from the police, solicit expert witness testimonies, and do laboratory analyses on the evidence as deemed necessary. Conclusion. According to the Decree of the Attorney General of the Republic of Indonesia No. 518/A/J.A/11/2001, dated November 1, 2001, which amends Decree No. 132/JA/11/1994 regarding the Administration of Criminal Cases, these codes serve as form codes utilized in the management and resolution of criminal cases. Implication. The community understands the flow of law enforcement.